Mapeamento do uso da terra, vegetação e impactos ambientais por meio de sensoriamento remoto e geoprocessamento - Ortiz, Jonas Luís; Freitas, Maria Isabel Castreghini de [UNESP] (My University, 2005)
The mapping of the land use, vegetation and environmental impacts using remote sensing ana geoprocessmg allow detection, spatial representation and quantification of the alterations caused by the human action on the nature, contributing to the monitoring and planning of those activities that may cause damages to the environment. This study apply methodologies based on digital processing of orbital images for the mapping of the land use, vegetation and anthropic activities that cause impacts in the environment. It was considered a test area in the district of Assistência and surroundings, in Rio Claro (SP) region. The methodology proposed was checked through the crossing of maps in the software GIS - Idrisi. These maps either obtained with conventional interpretation of aerial photos of 1995, digitized in the software CAD Overlay and geo-referenced in the AutoCAD Map, or with the application of digital classification systems on SPOT-XS and PAN orbital images of 1995, followed by field observations. The crossing of conventional and digital maps of a same area with the CIS allows to verify the overall results obtained through the computational handling of orbital images. With the use of digital processing techniques, specially multiespectral classification, it is possible to detect automatically and visually the impacts related to the mineral extraction, as well as to survey the land use, vegetation and environmental impacts.

O mapeamento do uso da terra, vegetação e impactos ambientais utilizando sensoriamento remoto e geoprocessamento permite detectar, espacializar e quantificar as alterações provocadas pelo homem na natureza, contribuindo para o monitoramento e planejamento de atividades que provocam ou possam provocar danos ao meio ambiente. O objetivo desse trabalho constituiu-se em aplicar metodologias que utilizem processamento digital de imagens orbitais para o mapeamento do uso da terra, vegetação e atividades antrópicas que causam impacto ao meio, considerando uma área teste que corresponde ao distrito de Assistência e entorno, no município de Rio Claro (SP). A metodologia proposta foi aferida por meio do cruzamento, no SIG – Idrisi, de mapas obtidos com interpretação convencional de fotografias aéreas de 1995, posteriormente digitalizados no software CAD Overlay e geo-referenciados no AutoCAD Map, e mapas obtidos por meio da aplicação de sistemas de classificação digital em uma imagem orbital SPOT-XS e PAN, ano de 1995, e trabalho de campo. Foi observado que o cruzamento de mapeamentos convencionais e digitais de uma mesma área, dentro de um SIG, possibilita a aferição dos resultados obtidos por meio de manipulação computacional de imagens orbitais. Concluiu-se que, com as técnicas de processamento digital utilizadas, principalmente classificação multiespectral, pode-se detectar automaticamente e visualmente impactos relacionados com extração mineral, bem como mapear o uso da terra, vegetação e os impactos ambientais.
Mapping of the land use, vegetation and environmental impacts through remote sensing and geoprocessing
Keywords: Environmental impact; Geoprocessing; Land use; Mapping; Remote sensing; Vegetation; computer aided design; environmental impact; human activity; mapping; remote sensing; SPOT; vegetation; Brazil; Rio Claro; Sao Paulo [Brazil]; South America